The role of prayer in reducing social risk behaviors among Muslim college students in Iran - Amir Qorbanpoorlafmejani; Sajjad Rezaei; Hamid qorbanpoorlafmejani (Health, Spirituality and Medical Ethics, 2021)
Background and Objectives: Although coping with risky behaviors (social delinquencies) consumes a substantial share of a nation's budget, but paying attention to these cases can lead to the prevention and treatment of these risky behaviors. The present study seeks to determine the main and interaction effects of gender and prayer behavior, as a recommended behavior in Islam, on the attitudes of students toward risk behaviors. Methods: This retrospective or ex post facto research was performed to investigate the effect of prayer on the tendency to social risk behaviors in 2019.For this purpose, 340 male and female students from University of Guilan (169 prayerful and 171 prayerless) who were selected through purposive sampling,   answered the Attitude toward Social Delinquencies Inventory of Aghaei and Teimurtash (2010). In order to determine the main and interaction effects of prayer and gender on the total score as well as the dimensions of attitudes to social delinquencies, one-way and multivariate analysis of variance were used in a 2×2 factorial design. Results: For the subscales, the findings showed that prayerless students were more prone to robbery, free sex relations, suicide and home escape. At the level of gender differences, regardless of prayer behavior, men were found to be more prone to free sex relations, and home escape than women. At the level of interaction effects, it was found that the interaction effect of group membership and gender was only significant on aggression. This means that the mean scores of aggression tendency were higher in the prayerless male group. Conclusion: These results confirm the protective role of prayer behavior in reducing the tendency to risk behaviors (especially aggression in the male group) in Muslim students of Iran.